2020
DOI: 10.1017/cjn.2020.162
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Determinants and Experiences of Senior Stroke Patients with Virtual Care

Abstract: Objective: The study sought to explore the experiences of participants affected by stroke with home video visit (HVV) for follow-up visits in order to understand the determinants, barriers, and benefits associated with HVVs. Methods: Semi-structured interviews were conducted with (n = 23) participants to gather insight and descriptive information about patients’ experiences with HVV. Specifically, we sought to collect descriptions about the (1) costs and time associated with in-person vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 24 publications
(37 citation statements)
references
References 12 publications
2
35
0
Order By: Relevance
“…In the context of being a new mother, participants felt that virtual visits were able to address many challenges unique to this population, such as scheduling difficulties, needing to arrange for childcare, and time constraints due to busier routines. These findings are consistent with previous literature, where patients found virtual care to be convenient, time-saving, and accessible for patients with unique physical impairments [ 15 , 26 ].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In the context of being a new mother, participants felt that virtual visits were able to address many challenges unique to this population, such as scheduling difficulties, needing to arrange for childcare, and time constraints due to busier routines. These findings are consistent with previous literature, where patients found virtual care to be convenient, time-saving, and accessible for patients with unique physical impairments [ 15 , 26 ].…”
Section: Discussionsupporting
confidence: 92%
“…This was particularly relevant throughout the ongoing COVID-19 pandemic, as patients were not permitted to bring other children to in-person visits in order to prevent unwanted exposure. These findings are also consistent with other studies exploring the use of virtual care in other patient populations, which support its use in alleviating the aforementioned barriers related to accessing in-person healthcare services [ 13 , 15 , 26 , 32 ].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Patients with cognitive impairment may require additional assistance in setting up physician consultations, while patients with limited dexterity may find physically operating these devices challenging. In our research, we have found that around 30% of our elderly patients that have conducted VC visits did not have an Internet-enabled device or required a caregiver to set up the program for them (12). Patients of a lower socioeconomic status or from developing nations may not have access to Internet-enabled devices.…”
Section: Case Illustrationmentioning
confidence: 90%
“…Some note that the switch to virtual care may make care more accessible [5][6][7][8] , while others have highlighted barriers certain populations face in accessing virtual care [9][10][11][12] . Prior studies suggest patient characteristics including older age and lower income may limit one's ability to benefit from digital health and virtual care services [13][14] . In addition, patients may not have access to required technologies such as a phone or internet access [15][16] .…”
Section: Introductionmentioning
confidence: 99%